2020
DOI: 10.4168/aair.2020.12.4.579
|View full text |Cite
|
Sign up to set email alerts
|

Skin Exposure Contributes to Chemical-Induced Asthma: What is the Evidence? A Systematic Review of Animal Models

Abstract: It is generally assumed that allergic asthma originates primarily through sensitization via the respiratory mucosa, but emerging clinical observations and experimental studies indicate that skin exposure to low molecular weight (LMW) agents, i.e. "chemicals," may lead to systemic sensitization and subsequently develop asthma when the chemical is inhaled. This review aims to evaluate the accumulating experimental evidence that adverse respiratory responses can be elicited upon inhalation of an LMW chemical sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Asthma is a chronic airway inflammatory disorder. 23 In this study, the risk of psoriasis was increased in patients with asthma. Few studies reported the association of asthma and psoriasis and these results were inconclusive.…”
Section: Discussionmentioning
confidence: 55%
“…Asthma is a chronic airway inflammatory disorder. 23 In this study, the risk of psoriasis was increased in patients with asthma. Few studies reported the association of asthma and psoriasis and these results were inconclusive.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to inhalation exposure, there is an obligation to assess dermal exposures in the worker exposure scenarios under REACH. The dermal route is of particular relevance when assessing the overall exposure to diisocyanates, as the role of skin exposure to diisocyanates for development of respiratory sensitization and occupational asthma is discussed ( Fent et al , 2009 ; Tsui et al , 2020 ). Cowie et al conducted a comprehensive study on where diisocyanates were used in the UK and found that the airborne diisocyanate exposure were minimal in almost all of the investigated workplaces, but ‘there was nearly always potential for skin contact’ ( Cowie et al , 2005 ).…”
Section: Scope and Methods Of The Assessmentmentioning
confidence: 99%
“…We and other groups already emphasized the importance of previous skin exposure in inducing a pronounced airway response. 43 44 45 46 …”
Section: Discussionmentioning
confidence: 99%